Playing the policy game: A review of the barriers to and enablers of nutrition policy change - Cullerton, K.; Donnet, T.; Lee, Andy; Gallegos, D. (Cambridge University Press, 2016)
© The Authors 2016. Objective To progress nutrition policy change and develop more effective advocates, it is useful to consider real-world factors and practical experiences of past advocacy efforts to determine the key barriers to and enablers of nutrition policy change. The present review aimed to identify and synthesize the enablers of and barriers to public policy change within the field of nutrition. Design Electronic databases were searched systematically for studies examining policy making in public health nutrition. An interpretive synthesis was undertaken. Setting International, national, state and local government jurisdictions within high-income, democratic countries. Results Sixty-three studies were selected for inclusion. Numerous themes were identified explaining the barriers to and enablers of policy change, all of which fell under the overarching category of 'political will', underpinned by a second major category, 'public will'. Sub-themes, including pressure from industry, neoliberal ideology, use of emotions and values, and being visible, were prevalent in describing links between public will, political will and policy change. Conclusions The frustration around lack of public policy change in nutrition frequently stems from a belief that policy making is a rational process in which evidence is used to assess the relative costs and benefits of options. The findings from the present review confirm that evidence is only one component of influencing policy change. For policy change to occur there needs to be the political will, and often the public will, for the proposed policy problem and solution. The review presents a suite of enablers which can assist health professionals to influence political and public will in future advocacy efforts.